2010
DOI: 10.1128/aem.02864-09
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Distribution of Ammonia-Oxidizing Crenarchaeota and Methanogens in the Epipelagic Waters of Lake Kivu (Rwanda-Democratic Republic of the Congo)

Abstract: over euryarchaeotal ones (7 OTUs). Sequences affiliated with the kingdom Euryarchaeota were mainly recovered from the anoxic water compartment and mostly grouped into methanogenic lineages (Methanosarcinales and Methanocellales). In turn, crenarchaeal phylotypes were recovered throughout the sampled epipelagic waters (0-to 100-m depth), with clear phylogenetic segregation along the transition from oxic to anoxic water masses. Thus, whereas in the anoxic hypolimnion crenarchaeotal OTUs were mainly assigned to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 81 publications
(62 citation statements)
references
References 82 publications
5
55
0
1
Order By: Relevance
“…Eluents were then passed through 0.22-μm pore size filters (ISOPORE, Millipore, MA) to retain free-living prokaryotes. Filters for DNA extraction were preserved in Lysis Buffer as previously described [21], whereas filters for RNA extraction were preserved in 300 μL of RNAlater (Ambion) and all stored frozen until further analyses.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eluents were then passed through 0.22-μm pore size filters (ISOPORE, Millipore, MA) to retain free-living prokaryotes. Filters for DNA extraction were preserved in Lysis Buffer as previously described [21], whereas filters for RNA extraction were preserved in 300 μL of RNAlater (Ambion) and all stored frozen until further analyses.…”
Section: Methodsmentioning
confidence: 99%
“…In spite of the presence of high amounts of CH 4 at the bottom of Lake Kivu, the CH 4 concentration in the oxic zone is surprisingly low compared to other lakes globally, due to intense microbial methane oxidation [18,19]. The vertical stratification of microbial taxa and their potential role in biogeochemical cycles in Lake Kivu were recently studied for both archaeal and bacterial counterparts using DNA-based analysis, and important key players of carbon, nitrogen, and sulfur cycles were identified [20,21]. Furthermore, evaluation of the effect of temporal variations on abundant versus rare taxa in different layers revealed that abundant taxa were more stable between two sampling times than rare ones, indicating a potentially higher contribution of rare taxa to biogeochemical processes [20].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the detection of archaeal ammonia monooxygenase subunit A ( amoA ) genes at the depths where maxima of nitrate and nitrite were observed in two basins of the lake (Fig. 6.1 ) points to the involvement of planktonic archaea in nitri fi cation processes in the oxycline (Llirós et al 2010 ) . Although con fi rmation by in situ activity measurements is still needed, available data suggest an active contribution of ammonia-oxidizing archaea (AOA) in the N cycle of Lake Kivu.…”
Section: Archaeal and Bacterial Assemblagesmentioning
confidence: 99%
“…The sharp oxycline and the oligotrophic nature of the lake's mixolimnion offer an optimal niche for the development of autotrophic nitrifying archaeal populations (Martens-Habbena et al 2009 ) . Llirós et al ( 2010 ) reported the recovery in Lake Kivu of a large set of sequences af fi liated to Marine Crenarchaeota Group 1.1a and assigned to a unique OTU (operational taxonomic unit) related to Nitrosopumilus maritimus , indicating the presence of active archaeal nitri fi ers in the lake water column. Furthermore, the detection of archaeal ammonia monooxygenase subunit A ( amoA ) genes at the depths where maxima of nitrate and nitrite were observed in two basins of the lake (Fig.…”
Section: Archaeal and Bacterial Assemblagesmentioning
confidence: 99%
See 1 more Smart Citation